CBT and positive psychology interventions for clinical depression promote healthy attentional biases: An eye‐tracking study. Issue 10 (20th July 2018) - Vazquez, Carmelo; Duque, Almudena; Blanco, Ivan; Pascual, Teodoro; Poyato, Natalia; Lopez‐Gomez, Irene; Chaves, Covadonga
Abstract : Background: Although there is a growing interest in the role of attentional biases in depression, there are no studies assessing changes in these biases after psychotherapeutic interventions. Methods: We used a validated eye‐tracking procedure to assess pre–post therapy changes in attentional biases toward emotional information (i.e., happy, sad, and angry faces) when presented with neutral information (i.e., neutral faces). The sample consisted of 75 participants with major depression or dysthymia. Participants were blindly assigned to one of two 10 weekly sessions of group therapy: a cognitive behavior therapy intervention ( N = 41) and a positive psychology intervention ( N = 34). Results: Both treatments were equally efficacious in improving depressive symptoms ( p = .0001, η² = .68). A significant change in attentional performance after therapy was observed irrespective of the intervention modality. Comparison of pre–post attentional measures revealed a significant reduction in the total time of fixations (TTF) looking at negative information (i.e., sad and angry faces) and a significant increase in the TTF looking at positive information (i.e., happy faces)—all p < .02. Conclusions: Findings reveal for the first time that psychotherapeutic interventions are associated with a significant change in attentional biases as assessed by a direct measure of attention. Furthermore, these changes seem to operate in the same direction typically found in healthy populations (i.e., a bias away from negative information and a parallel bias toward positive information). These findings illustrate the importance of considering attentional biases as clinical markers of depression and suggest the viability of modifying these biases as a potential tool for clinical change.